An Integrated System for Learning Quality Management Based on the Tridharma of Higher Education - Assingkily, Muhammad Shaleh; Putri, Noni (Lembaga Yasin AlSys, 2023)
The quality of learning is a crucial aspect that requires effective and efficient management. Often, learning quality management is seen as separate from the learning process, in fact, both are integrated. This study aims to describe the quality management of learning in an integrated system-based tertiary institution at STIT Al-Ittihadiyah Labuhanbatu Utara. This type of research includes qualitative with descriptive study method. Collecting data using interviews, observation, and document study. Furthermore, the data were analyzed using reduction techniques, data presentation and drawing conclusions. The results of this study obtained (1) the leadership of STIT Al-Ittihadiyah Labuhanbatu Utara designed an integrated system through a clear vision, mission and goals based on the tridharma of higher education, (2) development of materials and lecture materials based on assessment and certification (institutional accreditation); and (3) the campus quality assurance system establishes a self-assessment model. Thus, it is concluded that integrated system-based learning quality management at STIT Al-Ittihadiyah Labuhanbatu Utara is implemented effectively and efficiently.